Preventing fraud and corruption in World Bank projects : a guide for staff - Aguilar, Mario A.; Gill, Jit B. S.; Pino, Livio (Washington, D.C. : World Bank, 2000)
The guide is intended to enhance our awareness of the ways in which fraud and corruption may creep into projects and the measures that can be taken to counter them.
Includes bibliographical references (p. 52-53).
osa 11/4/19
Loans
Keywords: International finance; Banks and banking; Bank fraud